The neuron-specific interleukin-1 receptor accessory protein alters emergent network state properties in Vitro - Nguyen, Joseph T. (Neurobiol Sleep Circadian Rhythms, 2019)
Small in vitro neuronal/glial networks exhibit sleep-like states. Sleep regulatory substance interleukin-1β (IL1) signals via its type I receptor and a receptor accessory protein (AcP). AcP has a neuron-specific isoform called AcPb. After sleep deprivation, AcPb, but not AcP, upregulates in brain, and mice lacking AcPb lack sleep rebound. Herein we used action potentials (APs), AP burstiness, synchronization of electrical activity (SYN), and delta wave (0.5–3.75 Hz) power to characterize cortical culture network state. Homologous parameters are used in vivo to characterize sleep. Cortical cells from 1–2-day-old pups from AcP knockout (KO, lacking both AcP and AcPb), AcPb KO (lacking only AcPb), and wild type (WT) mice were cultured separately on multi-electrode arrays. Recordings of spontaneous activity were taken each day during days 4–14 in vitro. In addition, cultures were treated with IL1, or in separate experiments, stimulated electrically to determine evoked response potentials (ERPs). In AcP KO cells, the maturation of network properties accelerated compared to those from cells lacking only AcPb. In contrast, the lack of AcPb delayed spontaneous network emergence of sleep-linked properties. The addition of IL1 enhanced delta wave power in WT cells but not in AcP KO or AcPb KO cells. The ontology of electrically-induced ERPs was delayed in AcP KO cells. We conclude IL1 signaling has a critical role in the emergence of sleep-linked network behavior with AcP playing a dominant role in the slowing of development while AcPb enhances development rates of sleep-linked emergent network properties.